The Political Economy of Conditional and Unconditional Foreign Assistance : Grants vs. Loan Rollovers - Mayer, Wolfgang; Mourmouras, Alex. (Washington, D.C. : International Monetary Fund, 2004)
Improving the effectiveness of financial assistance programs is a priority of international financial institutions (IFIs). This paper examines the effectiveness of alternative assistance instruments in a dynamic political economy framework. Economic policies of the receiving country are distorted by the influence of a domestic interest group. The assistance-providing IFI aims at reducing these distortions. The IFI provides assistance either as grants or loans, and either conditionally on reducing policy distortions or unconditionally. The paper shows that, other things constant, one-time grants are more effective than loan rollovers when assistance is unconditional, but that the opposite is true when assistance is conditional.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Conditionality; Developing Country; IMF; Present Value; WP; United States